SATISFACTION OF SENIOR HIGH SCHOOL STUDENTS TOWARDS THE IMPLEMENTATION OF ENGLISH BLENDED LEARNING - DAVID BERTHONY MANALU; HANNA CRISTINA RUMAHORBO; WINDA SEPTRILI HUTAGALUNG; EDITH AFRILLIA HASIBUAN; MELI ASTRI DEMAK SIAHAAN (CV KULTURA DIGITAL MEDIA, 2022)
This research was aimed to find out the implementation of blended learning in teaching English. The design of this research was a survey research that was conducted in SMA Negeri 4 Pematangsiantar. The research instrument was 20 items of closed-ended questionnaire in order to find students’ satisfaction towards the implementation of English blended learning. The sample of this research was 102 students in the tenth grade of 2021/2022 Academic Year. It was found that the respondents were satisfied towards the implementation of English blended learning. The students considered that the blended learning was monotonous because it was just like the face-to-face learning. The teacher needed to add some activities to cope this problem. In conclusion, English blended learning has encouraged students to do collaborative, innovative, and creative learning.